2016
DOI: 10.1093/eurpub/ckw172.020
|View full text |Cite
|
Sign up to set email alerts
|

Trends in educational inequalities in obesity in 15 European countries between 1990 and 2010

Abstract: Background: The prevalence of obesity increased dramatically in many European countries in the past decades. Whether the increase occurred to the same extent in all socioeconomic groups is less known. We systematically assessed and compared the trends in educational inequalities in obesity in 15 different European countries between 1990 and 2010.Methods: Nationally representative survey data from 15 European countries were harmonized and used in a metaregression of trends in prevalence and educational inequali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 32 publications
0
19
2
Order By: Relevance
“…Socioeconomic status (SES) is among the strongest predictors of body weight, with strong inverse associations between indicators of SES and body mass index (BMI) found in numerous high income countries (Hoffmann et al . 2017). Recently, studies have started to investigate the importance of cultural capital for socioeconomic inequalities in BMI (Christensen and Carpiano 2014, De Clercq et al .…”
Section: Introductionmentioning
confidence: 99%
“…Socioeconomic status (SES) is among the strongest predictors of body weight, with strong inverse associations between indicators of SES and body mass index (BMI) found in numerous high income countries (Hoffmann et al . 2017). Recently, studies have started to investigate the importance of cultural capital for socioeconomic inequalities in BMI (Christensen and Carpiano 2014, De Clercq et al .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is not surprising that EIG for European/other women would start to decline earlier in time than those of other subpopulations. The negative relationship between BMI and educational attainment in high‐income countries is steeper for women than for men, suggesting a stronger influence of higher education on maintaining normal BMI .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the social distribution of cancer risk factors varies among countries and over time. [15][16][17] As a result, the association between SEP and cancer is not stable over time or across countries. Some studies have found a widening gap between SEP and all-cancer sites combined.…”
Section: Introductionmentioning
confidence: 99%